Hyoid Bone Suspension as a Part of Multilevel Surgery for Obstructive Sleep Apnea Syndrome - Tantawy,Abd Alzaher (2018)
Abstract Introduction Since oropharyngeal surgery alone is often insufficient to treat obstructive sleep apnea (OSA), advances have been developed in hypopharyngeal surgery. Objective To assess hyoid suspension surgery as part of amultilevel OSA surgery, also including palatal surgery. Methods The study included patients with OSA symptoms with apnea hypopnea index (AHI) > 15. They were scheduled for hyoid suspension after a nasoendoscopy during Müller maneuver and drug induced sleep endoscopy (DISE). All patients had body mass index (BMI) < 35 kg/m2. Hyoidothyroidopexy combined with tonsillectomy and palatal suspension was performed in all cases. Results The mean AHI dropped significantly (p < 0.0001) from 68.4 ± 25.3 preoperatively to 25.6 ± 9.52 postoperatively. The mean lowest oxygen (O2) saturation level increased significantly from 66.8 ± 11.3 to 83.2 ± 2.86 (p < 0.0001). In addition, the snoring score significantly decreased (p < 0.0001) from a preoperative mean of 3.4 ± 0.54 to 2 ± 0.7 at 6 months postoperatively. In regard to the Epworth sleepiness scale (ESS), it showed significant improvements (p < 0.0001) as its mean diminished from 13.8 ± 5.4 preoperatively to 5.2 ± 1.6 postoperatively. Conclusion Hyoidothyroidopexy using absorbable suture seems to produce a good outcome in treating OSA. It could be effectively and safely combined with other palatal procedures in the multilevel surgery for OSA.